Mental skills for young athletes - Archer, Mark; Thibault, Chris; Gould, Daniel; Virtual Brands ([Wilbraham, Mass.] : Virtual Brands, 2005)
Sport psychology consultant Daniel Gould, expert on mental skills training, discusses programs designed to help children ages 7 to 13 develop mental skills that contribute to success and enjoyment in sport
Includes extra sections for coaches and sport psychology consultants
Title from title screen
Executive producers, Britt Brewer, Al Petipas, Judy Van Raalte ; camera, Mark Archer, Chris Thibault ; content development, Daniel Gould, Kristen Dieffenbach
Host: Al Petitpas
Consultant: Danield Gould
Keywords: Sports for children -- Psychological aspects; Sports -- Psychological aspects; Athletes -- Psychology